2023
DOI: 10.1523/jneurosci.1341-22.2023
|View full text |Cite
|
Sign up to set email alerts
|

Activity-Dependent Nr4a2 Induction Modulates Synaptic Expression of AMPA Receptors and Plasticity via a Ca2+/CRTC1/CREB Pathway

Abstract: Transcription factors have a pivotal role in synaptic plasticity and the associated modification of neuronal networks required for memory formation and consolidation. The nuclear receptors subfamily 4 group A (Nr4a) have emerged as possible modulators of hippocampal synaptic plasticity and cognitive functions. However, the molecular and cellular mechanisms underlying Nr4a2-mediated hippocampal synaptic plasticity are not completely known. Here, we report that neuronal activity enhances Nr4a2 expression and fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 77 publications
1
11
0
Order By: Relevance
“…It is now widely accepted that oAβ are one of the initial mediators leading to early synaptic dysfunction in AD (Forner et al, 2017). Since we have previously reported that Nr4a2 has a key role in hippocampal synaptic plasticity (Català-Solsona et al, 2023), we wanted to address the eventual involvement of Nr4a2 in the synaptic failure occurring at early AD stages. For that purpose, we firs addressed whether oAβ could alter Nr4a2 levels in hippocampal neurons (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It is now widely accepted that oAβ are one of the initial mediators leading to early synaptic dysfunction in AD (Forner et al, 2017). Since we have previously reported that Nr4a2 has a key role in hippocampal synaptic plasticity (Català-Solsona et al, 2023), we wanted to address the eventual involvement of Nr4a2 in the synaptic failure occurring at early AD stages. For that purpose, we firs addressed whether oAβ could alter Nr4a2 levels in hippocampal neurons (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A mechanism involved in this effect is the oAβ-mediated decrease of surface expression of AMPARs (Hsieh et al, 2006; Minano-Molina et al, 2011). Since, we have recently reported that Nr4a2 activation increases postsynaptic AMPARs and effectively blocks LTD (Català-Solsona et al, 2023), we addressed whether Nr4a2 activation was able to rescue the oAβ-mediated deficits in hippocampal synaptic plasticity. We used the Nr4a2 activator amodiaquine (AQ) to test the effect of Nr4a2 activation on cLTD in primary cultures of hippocampal neurons (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Chemogenetic silencing of these neurons attenuates stress-induced anxiety- and depression-like behaviors in rodents 61 . Moreover, activity-dependent induction of NR4A2 can modulate AMPA-receptor mediated synaptic plasticity 82 whose alterations are strongly associated with depression 83 .…”
Section: Discussionmentioning
confidence: 99%